2010
DOI: 10.1038/mt.2010.152
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Expression and Activity of Sleeping Beauty Transposase in mouse liver following hydrodynamic DNA delivery

Abstract: The Sleeping Beauty (SB) transposon system can direct integration of DNA sequences into mammalian genomes. The SB system comprises a transposon and transposase that "cuts" the transposon from a plasmid and "pastes" it into a recipient genome. The transposase gene may integrate very rarely and randomly into genomes, which has led to concerns that continued expression might support continued remobilization of transposons and genomic instability. Consequently, we measured the duration of SB11 transposase expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…The subsequent slower loss of expression is most probably due to epigenetic silencing of integrated or unintegrated plasmids, coupled with slow cellular turnover and loss of unintegrated plasmids. This interpretation is consistent with what we find for expression of the Sleeping Beauty gene after hydrodynamic delivery (Bell et al, 2006). PEI-mediated toxicity in the lung is supported by the results from our quantification of excision products (Table 2).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The subsequent slower loss of expression is most probably due to epigenetic silencing of integrated or unintegrated plasmids, coupled with slow cellular turnover and loss of unintegrated plasmids. This interpretation is consistent with what we find for expression of the Sleeping Beauty gene after hydrodynamic delivery (Bell et al, 2006). PEI-mediated toxicity in the lung is supported by the results from our quantification of excision products (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…PEI-mediated toxicity in the lung is supported by the results from our quantification of excision products (Table 2). Normally, excision products are stable in the liver (Bell et al, 2006;Aronovich et al, 2007Aronovich et al, , 2009; but, as can be seen in the lower right quadrant of Table 2, over 7 days the number of excision products in the lung decreases more than 10-fold on a per-cell basis, which could be the result of cell death in those cells that took up PEI=DNA complexes. After 2-4 weeks, we observed that luciferase expression stabilized in both lung and liver when transposons were delivered with a source of transposase, which is consistent with expression from transgenes that have transposed into chromatin in the lungs (Belur et al, 2003;L.…”
Section: Discussionmentioning
confidence: 98%
“…In plasmids, reconstitution of the TTAA site posttransposition should result in the recircularization of the remaining linear backbones. Similar recircularization mechanisms have been described in systems other than pB (28,29). Recircularized plasmids remain in the nucleus and are thought to be degraded over time.…”
Section: Discussionmentioning
confidence: 72%
“…13,19,60 This suggests that 70-80% of plasmids in the liver are lost, but those that enter nuclei and are expressed are retained at a higher rate. In immunocompetent mice, further loss of activity/transfected cells occurs with the onset of adaptive immune responses.…”
Section: Discussionmentioning
confidence: 94%